Study on research progress of quartz-enhanced photoacoustic spectroscopy for trace gas detection - Chang, En-Qi; Wang, Gong; Li, Yun-Fei; Yu, Yu; Wang, Yulei; Lu, Zhiwei (Frontiers in Physics, 2025)
Real-time detection of trace gas concentrations has a wide range of applications in industrial processes and monitoring and various complex environments. Quartz-Enhanced Photoacoustic Spectroscopy (QEPAS) features high sensitivity and selectivity for the detection of single or multiple gases. It is immune to environmental noise and also boasts advantages such as miniaturization capability, ease of integration, and low cost. However, this technology also faces challenges such as limited laser source performance and the need to optimize quartz tuning fork (QTF) structural parameters. This paper reviews the current research progress in QEPAS, elaborating on its fundamental principle as well as the contributions from both laser source improvements (e.g., power, tuning range, and size) and QTF optimization (e.g., frequency, structure, and coating) to enhanced sensitivity. In addition, this paper systematically evaluates current research on auxiliary enhancement strategies, including relaxant selection, optical path and waveguide optimization, and dual-spectrum fusion. Finally, it summarizes existing technologies and proposes future prospects based on current technical bottlenecks.